Variations in composition and stability of biochars derived from different feedstock types at varying pyrolysis temperature - Abdulelah Abdullah Almutairi; Munir Ahmad; Muhammad Imran Rafique; Mohammad I. Al-Wabel (Journal of the Saudi Society of Agricultural Sciences, 2023)
Feedstock type and pyrolysis temperature primarily affect the properties of resultant biochar. Therefore, the effects of several different feedstock types and various pyrolysis temperatures on structural, chemical, proximate, morphological, and elemental compositional characteristics of the resultant biochars were explored. Nine types of wastes (date palm fiber waste (DF), date palm leaf waste (DL), date palm petiole waste (DP), tomato plant waste (TM), cucumber plant waste (CC), poultry litter (PL), chicken feather waste (CH), cow dung (CD), and conocarpus waste (CN) were collected and pyrolyzed at varying temperatures (300, 400, 500, and 600 °C) to produce different types of biochar, which were subjected to physio-chemical, proximate, and ultimate analyses. Distinctive variations were observed in the characteristics of the used feedstock types and their derived biochars. The biochars derived from CC exhibited the highest pH (8.41–11.02), while the biochars derived from CH demonstrated the minimum pH (7.99–8.40). Overall, the biochars derived from PL, CC, TM, and DL showed higher contents of C as compared to the other biochars, suggesting higher stability. Contrarily, the biochars derived from CH and CD exhibited a higher labile C fraction, indicating its lower recalcitrance than other tested biochars. The biochars produced at low pyrolysis temperatures showed a comparatively amorphous surface with lower alkalinity and electrical conductivity, while higher moisture, net negative charge, labile carbon, and volatile contents. Contrarily, the higher pyrolysis temperature demonstrated the higher ash and fixed carbon contents with more surface porosity and comparatively higher non-labile carbon fraction. Biochar produced at 600 °C exhibited H/C and O/C atomic ratios of <0.2, suggesting higher stability and recalcitrant potential against biochars produced below 500 °C, which showed H/C and O/C atomic ratios in the range of 0.2–0.4.